Strategic alignment of information technology and business - Coetze, Maarten Jacobus Petrus (My University, 2016)
The importance of information technology (IT) strategic alignment with organisational goals is considered and discussed. Internal and external factors that affect this alignment are identified. A method to strategically align business and IT is developed. A case study methodology was used, which relied on both quantitative and qualitative methods. The focus of the case study is the School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, South Africa. The research identified current IT alignment barriers and the special requirements of this domain by conducting interviews, using questionnaires and focusing on relevant strategic documentation. Data from the case-study environment was used to identify strengths, weaknesses, opportunities and threats. The researcher identified a lack of commitment on the part of management both within the School and in the broader University to the University’s strategic objectives as the main obstacle to IT and business strategic alignment. A revised IT strategic plan is developed for the School.
A dissertation Submitted in Fulfillment of the Requirements for the degree of Master of Science Engineering (Industrial Engineering) University of the Witwatersrand 2016
Keywords: Business logistics--Management; Information technology; Strategic planning